A Vps21 endocytic module regulates autophagy - Chen, Yong (The American Society for Cell Biology, 2014)
In autophagy, the double-membrane autophagosome delivers cellular components for their degradation in the lysosome. The conserved Ypt/Rab GTPases regulate all cellular trafficking pathways, including autophagy. These GTPases function in modules that include guanine-nucleotide exchange factor (GEF) activators and downstream effectors. Rab7 and its yeast homologue, Ypt7, in the context of such a module, regulate the fusion of both late endosomes and autophagosomes with the lysosome. In yeast, the Rab5-related Vps21 is known for its role in early- to late-endosome transport. Here we show an additional role for Vps21 in autophagy. First, vps21∆ mutant cells are defective in selective and nonselective autophagy. Second, fluorescence and electron microscopy analyses show that vps21∆ mutant cells accumulate clusters of autophagosomal structures outside the vacuole. Third, cells with mutations in other members of the endocytic Vps21 module, including the GEF Vps9 and factors that function downstream of Vps21, Vac1, CORVET, Pep12, and Vps45, are also defective in autophagy and accumulate clusters of autophagosomes. Finally, Vps21 localizes to PAS. We propose that the endocytic Vps21 module also regulates autophagy. These findings support the idea that the two pathways leading to the lysosome—endocytosis and autophagy—converge through the Vps21 and Ypt7 GTPase modules.